Long-term results of surgical treatment of the patients with Graves disease (toxic goiter) - M. B. Gudieva; S. Dora; E. I. Krasil’nikova; V. M. Sedov; A. R. Volkov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Analysis of the anamnestic data, of laboratory parameters and instrumental findings in 189 patients with toxic goiter, who had been operated on because of the lack of the disease remission, showed that during the period from 1970 to 2010, the number of relapses of hyperthyroidism after conservative surgery had increased seven times. The conclusion suggests further search for criteria of prognosing the results of surgical management